Edukasi Dini Berbasis One Health dalam Meningkatkan Kesadaran Kesehatan dan Lingkungan pada Siswa MI Al Fatah Gresik : Pengabdian - Yeshita Alifia Yuvianti; Lilis Sulistyorini; R. Azizah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The One Health approach emphasizes the importance of the interconnectedness between human, animal, and environmental health as an integrated effort for disease prevention and control. This community service activity aimed to implement the One Health approach through educational interventions for elementary school students at MI Al Fatah, Sukorejo Village, Sidayu District, Gresik Regency. The activity methods included material presentations, screening of educational videos, handwashing practice, and the administration of pre-tests and post-tests. The results showed an improvement in students’ understanding of the One Health concept, as evidenced by an increase in scores from 68.75% in the pre-test to 90.63% in the post-test. In addition, positive changes in clean and healthy living behaviors were observed, along with increased support from teachers to integrate this concept into learning activities. These findings indicate that an educational approach based on One Health is effectively implemented at the elementary school level and has the potential to serve as a sustainable community empowerment strategy.